Human Resources Management: Enhancing Teacher Professionalism as an Attempt to Realize Quality Generations - Mochamad Iskarim (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2016)
This study was descriptive qualitative research and aimed at investigating attempts for empowering teachers which were carried out by Madrasah Aliyah Nahdhatul Ulama (NU)Banyuputih, Batang. The teacher empowerment was intended to enhance the competences that should have been possessed, namely personal, pedagogical, professional, and social competences. Methods of data collection in this study employed interview and documentation. Likewise, this study applied Miles and Huberman’s Interactive Model of Analysis for analyzing the data. The results of this study reveal that Madrasah Aliyah Nahdhatul Ulama (NU)Banyuputih, Batang was very intensive in the teacher empowerment to create effective and humane learning in this madrasa. The teacher empowerment was organized in severalwell-scheduled, systematic, and sustainable activities. These activities were managed to improve the quality of teacher professionalism that was demonstrated with the mastery of four teacher competences, including pedagogical, personal, professional, and social competences.